N. Consani y Z. Zeraoui (comps.), Sobre Medio Oriente, Buenos Aires, Grupo Editor Latinoamericano, 2007, 278 pp. - Hodara, Joseph (Estudios de Asia y África, 2008)
N. Consani y Z. Zeraoui (comps.), Sobre Medio Oriente, Buenos Aires, Grupo Editor Latinoamericano, 2007, 278 pp.